DAMPAK PENERAPAN PROTOKOL KESEHATAN TERHADAP TINGKAT HUNIAN KAMAR DI HOTEL BINTANG 3 DAN 4 DI KOTA KUPANG - Laurensius Sandro Rero; Christina Mantolas (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2022)
The process of transitioning the COVID-19 outbreak from pandemic to endemic is still a question mark that has emerged until now, the impact is so visible, especially in the hotel industry, that the government, in this case the Ministry of Tourism and Creative Economy (Kemenparekraf) is starting to take concrete steps to restore the state of national tourism, one of which is by implementing a Health Protocol based on Cleanliness, Health, Safety and Environmental sustainability (CHSE). This protocol is an effort to welcome the new normal order and is one of the solutions to increase tourist confidence to return to tourism and encourage tourists to stay at hotels. The purpose of this study is to determine the impact of implementing the health protocol on room occupancy rates in the hotel industry in Kupang City, especially in 3 and 4 star hotels. The results of this study can become recommendations for tourism stakeholders in Kupang City in formulating policies to develop the tourism industry especially hospitality in the city of Kupang so that they can survive and develop in the new normal situation.